AN APPLICATION OF SANGHAHAWATTHU IV IN DEVELOPMENT THE QUALITY OF LIFE OF SAMAKKHITHAM TEMPLE COMMUNITY, KURABURI DISTRICT, PHANG NGA PROVINCE - Hitajitto, Phrakru Sutathammanusat; ., Pharkru Wijitrattanawat; ., Phrakru Kositwattananukul; ., Phrakru Sittisutakorn; (Sornma), Phra Likit Sukatito (Journal of MCU Nakhondhat, 2024)
The objectives of this research paper are to 1) Study the concept of improving the quality of life of the Wat Samakkitham community, Kuraburi District, Phang Nga Province, 2) Investigate the principle of Sangahavatthu in the Theravada Buddhist scriptures, and 3) Apply the Sangahavatthu in improving the quality of life of the community of Wat Samakkitham, Kuraburi District, Phang Nga Province. as a qualitative research. The researcher surveyed and collected data by in-depth interviews. Synthesize the results and present them in the form of descriptive narratives. Results were as follows: 1) Regarding the concept of improving the quality of life of the Wat Samakkitham community, Kuraburi District, Phang Nga Province, it is an improvement in the quality of life in 3 aspects: 1.1) The physical aspect with four requisites that are sufficient for living, 1.2) The emotional aspect, knowing how to control one’s emotions, and 1.3) The social aspect, being accepted and recognized by society 2) The principle of Sangahavatthu in the Theravada Buddhist scriptures is the doctrine of mutual relief consisting of Dana (charity), Piyavaca (amicable speech), Atthacariya (beneficial actions), and Samanattata (impartiality) 3) The application of the Sangahavatthu principle in in improving the quality of life of the community of Wat Samakkitham, Kuraburi District, Phang Nga Province is applied Physically, it will help create a happy and healthy society. Emotionally, it helps build mental stability. Strengthen good relationships in society. Socially, it will help strengthen good relationships in the community and create a just and peaceful society. In addition to bringing peace in our hearts It also results in unity and the development of a better life.